1974
DOI: 10.3402/tellusa.v26i1-2.9738
|View full text |Cite
|
Sign up to set email alerts
|

C<sub>1</sub>-C<sub>4</sub> hydrocarbons in the North and South Pacific<sup>1</sup>

Abstract: Low molecular weight hydrocarbons in the surface waters of the North and South Pacific have been measured. Methane concentrations average 4.2 x Inl/l, while the Cz-C, hydrocarbons averaged 1-5 x 10-6 ml/l. A large broad peak was found between 10" N and 10" S for the unsaturated hydrocarbons. Large concentrations of the C,-C, hydrocarbons were found in the different types of Antarctic sea ice. Atmospheric methane concentrations averaged 1.44 0.04 ppm and decreased t o 1.36 kO.04 pprn at the Intertropical Conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…Strong regional variations of ethylene concentrations in surface waters are observed in several studies of various marine areas including the Atlantic Lamontagne et al 1974;Plass et al 1992;Plass-Dülmer et al 1993, 1995. Investigations by Swinnerton and Lamontagne (1974) (Brooks & Sackett 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong regional variations of ethylene concentrations in surface waters are observed in several studies of various marine areas including the Atlantic Lamontagne et al 1974;Plass et al 1992;Plass-Dülmer et al 1993, 1995. Investigations by Swinnerton and Lamontagne (1974) (Brooks & Sackett 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Brooks and Sackett (1973) suggest that ethylene in the Gulf of Mexico is associated with primary productivity. Lamontagne et al (1974) assume variations of ethylene concentrations in the Pacific to be the result of biologic activity. Zang et al (1993) found indications for ethylene production in the red algae Porphyra perforata.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have been made concerning the occurrence of Cl to C4 hydrocarbons in seawater (Unnenbom and Swinnerton, 1970;Frank et aL., 1970;Lamontagne et al, 1971; Swinn.erton and Lamontagne et al, 1974;Lamontagne et al, 1976;Scranton, 1977). Methane typically occurs at about 30 ng/kg seawater (2.2 nM), ethane at 0.6 ng/kg (0.02 nM), and propane at 0.6 ng/kg (0.014 nM).…”
Section: Estimates Of the Size Of The Total Volatile Fractionmentioning
confidence: 99%
“…This process is of particular importance for those stations located at latitudes south of 30° S where the land surface and thus the continental C O production is negligible. The oceanic CO source strengths, either by direct CO emission from the oceans (Conrad et al, 1982) or by CO formation of hydrocarbons emitted from the ocean (Lamontagne et al, 1974(Lamontagne et al, , 1975Singh et al, 1978;Rudolph et al, 1982) are very small if compared with the total C O source strengths. Thus, the "excess CO" to balance the photochemical production and destruction of C O at 35"s must be advected from northerly latitudes.…”
Section: Hcho Chooh)mentioning
confidence: 99%